(untitled) (Ius Novum, 2024)
This article focuses on the European legal framework for environmental protection, in particular through criminal law. Given the societal need to reconcile technological development with the protection of natural resources and the environment in general, this is a highly relevant issue. The aim of this article is to describe and examine the current European legislation in the field of the environmental protection through criminal law, employing descriptive, analytical and synthetic methods. The article first discusses the history of environmental policy in public international law and European law, where initially the legal instruments of criminal law were not used. Subsequently, the author examines the current legal framework and, finally, considers its future. In the last parts, the article addresses the secondary law of the European Union, namely the Directive of the European Parliament and of the Council on the protection of the environment through criminal law of 2008 and the new Directive of the European Parliament and the Council on the criminal law protection of the environment of 2024. However, other decisions, directives and case law relevant to the issue are also covered. Overall, this is a unique article mapping all the essential legal instruments in the field of European environmental protection through criminal law. The author highlights the importance of protecting the environment through criminal law, but also emphasises the necessity of applying one of its basic principles, i.e., ultima ratio.